The Vascular System of the Albino Rat Iris, and Its Suitability for Vital Microscopy and Experimental Studies on Microcirculation - Castenholz, A. (Ophthalmic research, 2009)
In vital microscopy of the iris of the albino rat, 2 methods are available, quartz rod transillumination and illumination using the principle of the ophthalmoscope, making possible visualization of vascular and other structures even at high levels of optical magnification. Detailed morphologic and functional studies have revealed a characteristic angioarchitectural pattern and blood flow behavior in the rat iris, corresponding to its specialized functions (pupillo motoric activity, thermoregulation, etc.). Advantages and disadvantages of the living iris as a subject for general microscopic or microcirculatory studies are discussed in relation to the various organ-specific factors which characterize its vascular system